Friction and wear behavior of atmospheric plasma sprayed NiMoAl-Ag-hBN coatings at elevated temperatures - Singh A.K.; Atheaya D.; Tyagi R.; Ranjan V. (My University, 2025)
Several advanced technology applications i.e., gas turbine, aerospace and internal combustion engines, require the development of solid lubricating coatings which offer and maintain low friction and wear over a wide range of temperatures. Attaining effective lubrication over an extended regime of temperatures through a single lubricant is not possible. Hence, different combinations of solid lubricants are being explored. In the light of above, the present study is conducted to explore the synergy between silver (Ag) and hexagonal boron nitride (hBN) in obtaining the low friction and wear over a broad temperature ranging from RT to 800 °C. NiMoAl based coatings containing Ag, hBN or a combination of these were deposited on Inconel 718 via atmospheric plasma spray technique and their tribological performance was examined against alumina ball using a ball on disk arrangement at the fixed load of 5 N and constant sliding speed of 0.35 m/s using a high temperature rotary tribometer. The coating of base material i.e., NiMoAl exhibited the highest wear rate of 78.1 × 10−5 mm3/Nm at 600 °C which dropped to its lowest value of 7.9 × 10−5 mm3/Nm at 800 °C. The NiMoAl-Ag coating has the largest wear rate of 46.2 × 10−5 mm3/Nm at 400 °C, which reduces to its lowest value of 6.6 × 10−5 mm3/Nm at 800 °C. The wear rate for NiMoAl-hBN coating decreased continuously from 7.2 × 10−5 mm3/Nm at RT to 4.0 × 10−5 mm3/Nm at 800 °C. The NiMoAl-Ag-hBN showed the lowest wear rate among all the coatings which decreased with increasing temperature from RT to 800 °C, attaining a minimum wear rate of 3.20 × 10−5 mm3/Nm at 800 °C. NiMoAl-Ag-hBN not only exhibited the lowest coefficient of friction but also maintained a nearly constant value over the entire range of temperature from RT to 800 °C with the lowest friction coefficient of 0.15 at 800 °C. The improved tribological performance of NiMoAl-Ag-hBN coating has been accredited to synergistic action of Ag and hBN along with the development of lubricious oxides like NiO, MoO3, NiMoO4, Ag2MoxOy and the presence of hBN o the worn surface. © 2023 Elsevier B.V.